Reducing Energy Consumption of Methanol Production from Syngas by Modifying Heat Transfer Process - Putri, Aulya Fauzia; Arianti, Dina Fitri; Rahayu, Parastika Triana; Azizi, Rafi Hafizh (Journal of Chemical Engineering Research Progress, 2025)
Methanol is extensively used in the various products, including plastics, paints, adhesives, and synthetic fibers. With the many uses of methanol, its production must have high efficiency both in terms of energy and mass in order to obtain maximum profits. In this paper, we will explain how to reducing energy consumption and maximize methanol product yield by modifying the methanol synthesis. The process modification was carried out by adding heat exchanger, distillation column unit and recycle stream. Case study tools on chemical engineering software were used. Based on process modifications, an increase in methanol yield was obtained from 97.47% to 99%, the total energy savings from this process after adding distillation column is 57.618 × 106 kJ/h or 58.5% of the total initial energy, and with recycle stream the syngas produced reached 5.419 kgmol/h while without recycle stream, the syngas produced was only 4.157kgmol/h. The results of the case study indicate that the addition of heat exchanger, distillation column, and recycle stream is beneficial for the methanol production process by reducing the energy and increasing mass efficiency. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).